TEACHERS ATTITUDE TOWARDS ACCOMMODATING STUDENTS LEARNING STYLES CASE OF 2ND YEAR EFL STUDENTS AT MSILA UNIVERSITY - Ahmed BENTHAMEUR.Fatima TOUILE, Mrs. HAMOUMA (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
ABSTRACT The current study aims to investigate the effectiveness of considering learning styles in EFL student's academic achievement. That , It is generally accepted that knowing a student's preferred methods of learning can be advantageous for both students and teachers. It seems hard to alter each student's preferred learning method in the classroom because pupils learn in a variety of ways. The investigation is concerned with the case of second year EFL students at Msila university. In order to test our hypotheses , Two online questionnaires were administered for both EFL students and teachers. The data collected from the instruments used were based on qualitative and quantitative methods. The results gained endicate that learning styles raise students skill levels in EFL instruction when taken in consideration , and play a significant role in teaching English , and that teachers are aware of the matter. Further more, In order to accommodate varied learning styles, it is also advised that teachers adopt a balanced approach to their teaching methods. The study adopts a theoretical methodology to analyze pertinent literature on the subject and give several viewpoints on how learning styles and teaching styles can be matched or mismatched.
Keywords: Keywords: Learning styles, Teaching styles, Accommodating.